The Role of Sharia Compliance in Online Shop Applications in Improving Consumers’ Trust - Sriani, Endang; Hasanah, Nidaul; Mustofa, Ubaedul (IQTISHADIA, 2022)
Muslim business transactions are governed by the principles of Islamic values, specifically Sharia compliance. However, accommodating these values poses a challenge for modern transaction system providers. This is because online shop providers have not been considering Sharia compliance as a crucial aspect to enhance consumer confidence, especially among Muslim consumers. Therefore, this research aims to determine the extent to which sharia conformity of web features and online shop applications influences consumers’ trust in the online shopping platform. It is a quantitative analysis that uses primary data from respondents representing the population. The research population comprises users of online shop applications that apply sharia compliance principles in their web design with sample data of 430 respondents. Furthermore, the data analysis uses linear and multiple regression methods aided by SPSS data analysis tools. The results show a positive and significant influence between sharia compliance, specifically avoiding prohibitions, object & price, buyer & seller, as well as offering & acceptance in websites design or online shop applications on consumers’ trust both partially and simultaneously. The partial influence of each sharia compliance variable is avoidance of main prohibitions, object & price, buyer & seller, as well as offer & acceptance by 60.6%, 62.6%, 69.3%, and 57.2%, respectively. Meanwhile, the simultaneous influence of sharia compliance variables on consumers’ trust is 79.4%, and other variables influence the remaining 20.6%. These results suggest that online shop consumers, specifically Muslims, make sharia values an essential criterion for selecting and using online shops. The theoretical contribution is to build and strengthen the concept and theory of sharia compliance to construct consumer trust. Concerning the practical contribution, the results could be the basis of consideration for online shop service providers to increase consumers’ trust by providing services in line with sharia compliance principles. Further research could explore additional variables that affect consumers’ confidence in using online shop platforms.